Enhanced Hysteresis-Based Current Regulators in Vector Control of DFIG Wind Turbines - Mohseni, Mansour; Islam, Syed; Masoum, Mohammed (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2010)
This paper proposes enhanced hysteresis-based current regulators in the field-oriented vector control of doubly fedinduction generator (DFIG) wind turbines. The proposed control scheme is synchronized with the virtual grid-flux space vector, readily extractable by a quadrature phase-locked loop (QPLL) system. Identical equidistant-band vector-based hysteresis current regulators (VBHCRs) are then used to control the output currents of the rotor-side and grid-side converters. The proposed hysteresis based technique has excellent steady-state performance and reveals several advantages in comparison with the commonly used proportional-integral (PI) current regulator, including very fast transient response, simple control structure, and intrinsic robustness to the machine parameters variations. Moreover, the fixed hysteresis bands in VBHCRs are replaced with equidistant bands to limit the instantaneous variations of the switching frequency and reduce the maximum switching frequencies experienced in the converters. Extensive simulation studies are carried out for a 1.5MW DFIG-based wind turbine to examine the operation of the proposed vector control scheme under changing wind speed and compare its transient and steady-state performances with the conventional PI current regulators.